Evaluation of a Study Skills Program for Student-Athletes - Whitner, Phillip A.; Sanz, Donald L. (My University, 1988)
In response to an outcry from University professors and administrators regarding academics and athletics, the Athletes Educational Planning Program (AEPP) was developed. During the 1982-83 academic year the University of Toledo Counseling Center extended its voluntary study skills program to a specific University population-student-athletes (Danchise, 1985). The plan of the AEPP was to provide incoming freshmen male and female student-athletes with a traditional study skills program. A major goal of the program was to assist the freshman student-athlete in adjusting and in adapting to the academic ngors of a college environment through the utilization of study skills. The purpose of the evaluation was to determine if the program was having a positive effect on the student-athletes' academic performance. More specifically, "Was the intervention of the study skills program having a positive impact on the GPA's of student-athletes who participated in the program?" Low and moderate-risk student-athletes that participated in the program had a higher mean GPA than student-athletes in the same two categories who did not participate in the program. Borderline and high-risk student-athletes that participated in the program had a lower mean GPA than student-athletes in the same two categories who did not participate in the program. The mean GPA's in the last two categories, borderline and high-risk, were somewhat mystifying because the findings were contradictory to self-reports and observations. In order to determine if the program was having a positive effect on student-athletes' academic performance, it appeared that more than mean GPA's were needed.
Keywords: academic performance; at-risk; skills